Grease or Sand in the Wheels of Commerce? Firm Level Evidence on Corruption and SMES. (18th March 2015) - Mendoza, Ronald U.; Lim, Ricardo A.; Lopez, Anne Ong
Abstract Bribes can either put 'grease' or 'sand' in the wheels of commerce, affecting firm performance (at the micro‐level) and, ultimately, economic growth (at the macro‐level). This study examines this issue using a unique and exceptionally rich dataset on over 2000 micro, small and medium scale enterprises in over 30 cities in the Philippines. Using instruments such as industry‐location averages of corruption to deal with endogeneity and drawing on unique contextual information on public–private interactions on bribery, this study finds evidence that corruption greases the wheels of commerce for Philippine SMEs, particularly in cities with poor business environments. Copyright © 2015 John Wiley & Sons, Ltd.